Effect of petrographic composition and chemistry of aggregate on the local and general fracture response of cementitious composites - M. Vyhldal; I. Rozsypalov; H. imonov; B. Kucharczykov; P. Rovnankov; Z. Kerner; L. Vavro; M. Vavro; J. Nemecek (Fracture and Structural Integrity)
This paper concerns the results of research into the influence of the composition of rock inclusions on the fracture response of cement-based composite specimens. Specially designed specimens of the nominal dimensions 40 40 160 mm with inclusions in the shape of prisms with nominal dimensions of 8 8 40 mm were provided with an initial central edge notch with a depth of 12 mm. These specimens, which were made of fine-grained cement-based composite with different types of rock inclusion amphibolite, basalt, granite, and marble were tested in the three-point bending configuration. Fracture surfaces were examined via scanning electron microscopy and local response in the vicinity of rock inclusions was characterized via the nanoindentation technique. The aim of this paper is to analyse the influence of the chemical/petrographic composition of rock inclusions on the effective mechanical fracture parameters of cement-based composites, as well as on the microstructural mechanical parameters of the interfacial transition zone. The results of this research indicate the significant dependence of the effective fracture parameters on the petrographic and related chemical composition of the rock inclusions.